A holistic–integrative approach of the Muhammadiyah education system in Indonesia - Hamami, Tasman (HTS teologiese studies, 2022)
The Islamic education curriculum in Indonesia tends to be partial and dichotomous. However, Muhammadiyah has reformed the holistic–integrative curriculum as a solution for the sustainability of education. This study aims to reveal a special curriculum reform in the holistic–integrative Muhammadiyah education system to solve the dichotomous problems and the inadequacy in the Islamic education curriculum in Indonesia. Furthermore, the study describes a specific curriculum model that includes all aspects of students’ personality and integrates science and technology with Islamic values. Data were collected from previous studies and special curriculum documents of Al-Islam, Kemuhammadiyahan and Arabic Language (ISMUBA). Curriculum documents were obtained from elementary, junior and Muhammadiyah senior high school, published by Primary and Secondary Education Assembly of Muhammadiyah Central Board in 2017. Data analysis used a content model with a systematic and rational framework. The results showed that the special reform curriculum based on the holistic–integrative model develops students’ potentials, including spiritual, emotional, intellectual and transcendental intelligence, in an integrated manner.Contribution: The holistic–integrative curriculum is a future Islamic education model for the sustainability of private Islamic education system in Indonesia that can form a good, faithful, pious and a noble community.